High-risk basal cell carcinoma excision in primary care: a retrospective observational study of compliance with NICE guidance. Issue 11 (2nd December 2018) - Cole, Simon John; Howes, Rachel; Meehan, Chris; Cole, Richard
Abstract : Objectives: To assess compliance with 2010 National Institute for Health and Care Excellence (NICE) guidance on cancer services relating to the management of basal cell carcinomas (BCC) in the community, where except in specific circumstances it is recommended that only low-risk BCCs should be excised routinely. Design and setting: A retrospective observational study of the histopathology reports of BCC excisions received from primary care in two district general hospitals in the South of England. One hundred consecutive BCC excisions were analysed from each hospital. Outcome measures: The numbers of high-risk BCCs excised in primary care according to histological subtype, anatomical site and age and if these excisions were compliant with NICE 2010 guidance. Completeness of excision and mention of BCC on histology request were secondary outcomes. Results: Histologically high-risk subtypes were present in 32% (64/200) of BCCs excised in the community. Only 17/64 were excised by general practitioners (GPs) who were accredited to do so. Non-compliance regarding anatomical site occurred in 16% of samples; only one was non-compliant regarding patient age. There was a high overall rate of complete excision (94.5%) with variation in presence of the term BCC on histology request forms. Conclusions: NICE 2010 guidance relating to BCC excision in primary care was not followed in a considerable number of cases. Compliance with NICE 2010 guidance depends on the ability to recognise high-risk BCCs clinically and manage appropriately. It also shows that despite close supervision by secondary care, there are still failures of compliance. GP training in identification of subtypes of BCC might be improved, as well as an increase in numbers of GPs accredited to carry out high-risk BCC excisions. Difficulty in diagnosing high-risk histological subtypes of BCC preoperatively should be considered in any future revision of NICE guidance.